A Small-Molecule TrkB/TrkC Ligand Promotes Neurogenesis and Behavioral Recovery Following Traumatic Brain Injury - Jian Shi; Tao Yang; Yibing Li; Lily Zhong; Frank M. Longo; Stephen M. Massa (Neurotrauma Reports)
Tropomyosin receptor-kinase B (TrkB) and TrkC neurotrophin receptors promote neuronal growth and differentiation during the development and maintenance of structural integrity and plasticity in adult animals. Here, we test the hypotheses that activation of TrkB and TrkC will mitigate neuronal damage and loss, and behavioral deficits induced by traumatic brain injury (TBI). LM22B-10 (C10), a blood–brain barrier permeant small-molecule TrkB/TrkC co-activator, significantly increased proliferation, survival, and enhanced differentiation of neuronal progenitor cells in vitro. Following controlled cortical impact injury in rats, LM22B-10 administration increased the proliferation of doublecortin-expressing (DCX) cells in the hippocampus and significantly reduced cell death in the injured cortex. Interestingly, in studies of behavior, LM22B-10 promoted anxiety-like behavior and diminished spatial memory performance in the Barnes maze in sham-TBI animals but improved both of these behaviors in injured rats, a bimodal response suggesting the possibility that excess neurotrophic activity may be detrimental in uninjured animals but compensatory after injury. Thus, TrkB/TrkC agents may constitute a new therapeutic avenue for TBI but will require further study to determine safe and effective applications.